(untitled) (Journal of Parents and Teachers, 2026)
The authors of the article compiled the responses of 100 students from a state vocational college and Year 13 pupils from a private school in La Coruña. The questionnaire on adolescents’ emotional life and social skills concluded with a single open-ended question asking what friendship meant to them. The responses were varied yet consistent.